Estudio de la Dispersión en Campo del Macho estéril de la Mosca del Mediterráneo (ceratitis capitata) en la Provincia de Tungurahua en el periodo marzo – agosto 2019. - Alajo Silva, Adrián Alejandro (2019)
The present investigation evaluated the release of the sterile male Mediterranean fruit fly in two localities: Puñapi in Canton Patate and Quillán in Canton Píllaro in Tungurahua province, with the intention of determining its behavior and the climatic factors that influence its dispersion and distribution. In order to measure behavior, the frequencies of the habits of sterile insects were measured. As a result, a directional pattern towards the Northwest showed a greater concentration of captures at distances of 50 and 150 meters. It was concluded that in both localities, the most influential factors in the dispersal process of C. Capitata W, were mainly wind speed and direction, which favors the species to reach considerable ranges of dispersion and infested hosts. The obtained results constitute a contribution to the knowledge of the habits of the species, which must favor the optimization of the resources used in the control of the pest, on having allowed the elaboration of strategies with scientific foundations.